Remarkable decrease in lattice thermal conductivity of transition metals borides TiB2 by dimensional reduction. (4th June 2022) - Li, Ding; Hu, Yanxiao; Ding, Guangqian; Feng, Chunbao; Li, Dengfeng
Abstract: Two-dimensional transition metals borides Ti x B x have excellent magnetic and electronic properties and great potential in metal-ion batteries and energy storage. The thermal management is important for the safety and stability in these applications. We investigated the lattice dynamical and thermal transport properties of bulk-TiB2 and its two-dimensional (2D) counterparts based on density functional theory combined with solving phonon Boltzmann transport equation. The Poisson's ratio of bulk-TiB2 is positive while it changes to negative for monolayer TiB2 . We found that dimension reduction can cause the room-temperature in-plane lattice thermal conductivity decrease, which is opposite the trend of MoS2, MoSe2, WSe2 and SnSe. Additionally, the room temperature thermal conductivity of mono-TiB2 is only one sixth of that for bulk-TiB2 . It is attributed to the higher Debye temperature and stronger bonding stiffness in bulk-TiB2 . The bulk-TiB2 has higher phonon group velocity and weaker anharmonic effect comparing with its 2D counterparts. On the other hand, the room temperature lattice thermal conductivity of mono-Ti2 B2 is two times higher than that of mono-TiB2, which is due to three-phonon selection rule caused by the horizontal mirror symmetry.